Pengaruh Human Resource Development dan Job Security Terhadap Organizational Commitment pada Pekerja Generasi Z di Kota Samarinda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the Influence of Human Resource Development and Job Security on Organizational Commitment among Generation Z workers in Samarinda City. As a new generation entering the workforce, Generation Z possesses unique characteristics that affect their attachment to organizations. This research employs a quantitative method, utilizing questionnaires as the primary instrument to collect primary data from respondents selected through a random sampling technique. Data analysis is conducted using validity tests, reliability tests, multiple linear regression analysis, and classical assumption tests. The research findings are expected to contribute to the development of more effective human resource management strategies to enhance organizational commitment among young workers in the modern era.